GE_GERICHTE C/3243/2013 vom 22. Dezember 2016 - GE Cour de justice (2016)
RECOURS JOINT ; CONTRAT D'ARCHITECTE ; HONORAIRES ; DILIGENCE ; DEVIS ; DOMMAGES-INTÉRÊTS ; FRAIS JUDICIAIRES ; RÉPARTITION DES FRAIS | CO.394.3; CO.368.2; CPC.106.1; LaCC.19;